If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+19=3-5x*
We move all terms to the left:
3x+19-(3-5x*)=0
We add all the numbers together, and all the variables
3x-(-5x*+3)+19=0
We get rid of parentheses
3x+5x*-3+19=0
We add all the numbers together, and all the variables
3x+5x*+16=0
We move all terms containing x to the left, all other terms to the right
3x+5x*=-16
| -28-5-3x=2-2x | | -20+15j=-11-9+15j | | 3t−2+t−5 | | 3t−2+t−5 | | 8.33-6.6s+11.98=-18.75-8.7 | | 2x-1-16x-12=39 | | 5=x^2+2 | | 4(2r+8)+5r=13r+3 | | (9x-2)=(4x) | | -5+7(n+7)=93 | | 4(1-8r=-27-r | | r-13-9r=-13-7r | | (4x+17)+(7x-12)=180 | | -9-9j=19+17j-2 | | 5x+2x-9=61 | | w-19=-9 | | 17+2c=5c-8 | | 5x-1=-4x+2 | | 4m-9=6m+3 | | 9+m/3=22 | | -19-20d-19=17-15d | | 7(t+7)=-14 | | 3x^2+1=- | | 180-6x=+8x | | 7-18k=-10k+15-8k | | 30.7−x=20 | | 10m+7=31+4m | | -4=x^2-2x-15 | | X-1=3x-5-2x | | 5+7b=-16 | | 3x+5x^2=-6x+8x^2 | | 13x=10+12x |